Subsequent Fertility of Goats with Prenatal Mortality Diagnosed by Ultrasound and Treated by PGF2α and Oxytetracycline - A. S. Aban; R. M. Abdelghafar; M. E. Badawi; A. M. Almubarak (Veterinary Medicine International)
Thirteen Saanen and Saanen crossbred female goats, between the ages of 6 months and 7, years were presented to the clinic, College of Veterinary Medicine, Sudan University of Science and Technology, for sonographic pregnancy diagnosis. Transabdominal ultrasound was performed using 3.5 MHz probe which revealed non-viable fetuses as judged by absence of heart beats and movements. Twelve goats were given single i/m injection of PGF2α analogue and 5% oxytetracycline. Ten goats responded to the treatment and six of them became pregnant and gave birth within the normal gestational period. One goat was diagnosed as non-pregnant, one goat developed hydrometra, and the subsequent fertility of two goats was unknown. Two full-term goats did not respond to treatment. Another dose of PGF2α was administered to them and again they did not respond. Manual attempts were done to deliver the full-term goat with dilated cervix and they were unsuccessful. Cesarean section and hysterectomy were then performed for the three full-term goats with unfavorable outcome. It can be concluded that ultrasound is a rapid, reliable, and nonhazardous procedure for the diagnosis of fetal mortality in goats and PGF2α treatment in conjunction with oxytetracycline is an efficient treatment.